The Effect Of Changing Government Spending On Narrow Cash Supply In Iraq For The Period 2006-2018 - Obaid Juma’a, Abdul Rahman; Talib Muhammad, Mushtaq (Opción, 2020)
The research aims to analyze the effect of the change in government spending on the narrow money supply in oil countries, in which the narrow money sup- ply is dependent on the size of government spending. There is an effect that the change in government spending in oil countries will have on the narrow money supply. The most important objective of monetary policy is to stabilize prices through managing the money supply, because an increase in the money supply leads to an increase in inflation rates. One of the conclusions is that there is a short and long-term balance relationship between public spending and money supply. One of the recommendations is the necessity for coordina- tion between the monetary and fiscal policies in order to unify the goals.